Kontribusi Peer Attachment terhadap Dinamika Kelompok dalam Layanan Psikoedukasi: Studi Tinjauan Pustaka - Rasyidah Salsabila, Sofia; Muslikah (Jurnal Bimbingan dan Konseling Pandohop, 2026)
Individuals experience a transitional phase during adolescence, in which peer figures begin to replace or complement parents as primary sources of emotional support. This study aims to examine the role of peer attachment in group dynamics within psychoeducational services. This study employed a narrative literature review by examining research articles obtained from Google Scholar, Springer, Wiley, ScienceDirect, SAGE Journals, and Frontiers databases published between 2021 and 2025. Based on strict inclusion criteria related to peer attachment and psychoeducation, eleven primary articles were selected for qualitative descriptive analysis, consisting of eight articles on peer attachment and three articles on psychoeducation. The findings indicate that the dimensions of trust, responsive communication, and low levels of alienation can serve as crucial foundations for psychological safety in driving group dynamics. Secure peer attachment provides a psychological safety foundation that promotes self-disclosure and problem-solving skills within the group. Furthermore, positive peer attachment can function as a buffering mechanism against traumatic experiences among adolescents, thereby enhancing participants’ resilience and emotional regulation. The integration of healthy attachment into psychoeducation can create a supportive ecosystem for sustainable mental well-being.